Aerosol‐deposited Al2O3/PTFE hydrophobic coatings with adjustable transparency. Issue 4 (14th December 2020) - Kim, Ik‐Soo; Cho, Myung‐Yeon; Jeong, Yohan; Shin, Yun‐Cheol; Lee, Dong‐Won; Park, Chulhwan; Koo, Sang‐Mo; Ho Shin, Weon; Yang, Won‐Jik; Park, Yeol; Sohn, Hiesang; Oh, Jong‐Min
Abstract: With the wide range of requirements for architectural glass, such as transparency, opacity, and hydrophobicity, there is a need to address the issues in the complexity of convention methods. Thus, considering functionality and applicability in various architectural windows, hydrophobic alumina/polytetrafluoroethylene (Al2 O3 /PTFE) composite layers with transparency or opacity were transferred to commercial architectural glass using a facile aerosol deposition (AD) process. We successfully fabricated hydrophobic coating layers with high transmittance (only a 0.03% difference from sheet glass) by optimizing the PTFE content in Al2 O3 using solution‐based synthesized powders to enable a uniform surface topology. The opaque hydrophobic Al2 O3 /PTFE coating layers exhibit a transmittance of approximately 0% with excellent hydrophobicity of 130°. Remarkably, this opaque film was successfully employed onto a large deposition area, curved substrate, and micro‐patterned regions. It is believed that our AD‐prepared composite layers have great potential for architectural glass in terms of economic feasibility and versatility.